(untitled) (Malaysian Journal of Civil Engineering, 2018)
Fiber-reinforced polymer (FRP) composites have been used over few decades for structural repair and strengthening schemes for structural element but only optimized the applications recently. This paper presents a concise state-of-art review of the extensive research on reinforcing techniques using FRP for construction applications in civil engineering for last two decades. This review was focusing in flexural strengthening techniques applied for concrete, metal and timber structures by experimental and numerical analytical programs. The experimental specimens used by researchers vary from the existing elements structure and new invention for laboratory program only. Data and information collected in this review were gathered from the previous researches all over the world with some of them are applied to the real applications at construction sites. The review hoped to be a good reference and guidelines for all engineers and researches in fields of composites material especially fiber-reinforced polymer to enhance the application of FRP for new construction or rehabilitation of existing structure.